Recent progress of cassava varietal improvement in Indonesia - Poespodarsono, Soemarjo; Widodo, Yudi (International Center for Tropical Agriculture, 1995)
The role of cassava in Indonesia is becoming more important, whether it is used for food, for industrial processing or for export. The government of Indonesia has established two policies in the agricultural sector, namely: food diversification and increased productivity in the uplands. Food diversification is needed to reduce dependency on rice as the principal food by way of utilizing various other carbohydrate sources, especially cassava. The policy to increase productivity in the uplands, on the other hand, is launched because the acreage of lowland rice fields has been declining over the years with the conversion of some of this land to non-agricultural use, especially on Java. One way of increasing productivity in the up lands is through crop diversification. However, this diversification program should not affect the current productivity of cassava, since cassava has always functioned as a dominant commodity produced in the uplands. For this reason, the intensification of cassava becomes necessary, through, for example, application of intercropping systems that use suitable plant types, varieties as well as appropriate cultural technologies. Efforts to improve cassava cultivars should be made and the methods to introduce them to the farmers should be improved. When cassava is meant to substitute for rice as a source of carbohydrate, a high-quality cultivar, characterized by low HCN in the roots, needs to be developed. On the other hand, when it is meant for industrial use, a high-yielding cultivar with high starch content, needs to be developed. Special cultivars may also need to be developed when cassava is to be grown under intercropping systems. Cassava breeding in Indonesia is presently done jointly by MARIF, CIAT and Brawijaya University in Malang. MARIF has recently released two new high-quality cultivars, named Malang 1 (parents: CM1015-19 x CM849-1) and Malang 2 (parents: CM922-2 x CM507-37). The selection program carried out by Brawijaya University has produced a number of promising cassava clones, labelled UB 1-2 (parents: MCol 22 x CM849-1), UB 15-10 (parents: CM586-1 x CM523-7), UB 477-2 (parents: CM1002-4), UB 881-5 (parents: CM849-1) and UB566-8 (parents: MBra 35). These clones show their greatest potential in the uplands of subhumid regions like East Java. UB 477-2 is a sweet clone, while clones UB 15-10 and UB 566-8 are suitable for growing under intercropping systems. These promising clones will not be released as high-quality cultivars before they undergo multi-location trials in at least 5 provinces, as stipulated by the Minister of Agriculture of the Republic of Indonesia.